A racing heart post‐Pfizer/BioNTech BNT162b2. Issue 5 (5th September 2022) - Teo, Hooi Khee; Ho, Kah Leng; Tan, Boon Yew; Ching, Chi Keong; Chong, Daniel Thuan Tee
Abstract : Palpitations is one of the most common side effects experienced post‐messenger‐RNA COVID‐19 vaccines. However, some patients experience significant symptoms and further workup needs to be considered. We present an interesting case of inappropriate sinus tachycardia in a fit gentleman who presented with worsening palpitations and elevated heart rate post‐first and ‐second dose of the Pfizer/BioNTech vaccine.